An Empirical Study of Customer Satisfaction and Loyalty: An Evidence of Telecom Sector in Pakistan - Arman Khan; Javed Ahmed; Farman Ullah Khan (Journal of Business & Tourism, 2021)
This research explores key determinants of customer loyalty in a research setting where customer loyalty is a dependent variable and service quality switching costs and switching cost and trust are all independent variables. The research uses a variety of statistical techniques, including reliability factor and regression analysis. As the country is moving fast towards digital financial inclusion. The telecommunication sector in Pakistan has also been impressively keeping up with paced. With the growing fame of digital telecommunications, the evaluation of customer loyalty and satisfaction has become essential for mobile network operators as well as for researchers at the same moment. To define, the variables influencing client satisfaction and loyalty, a comprehensive literature study was conducted. A conceptual research model was created based on a literature review to identify the link between service quality and customer satisfaction, in addition to price switching, customer loyalty and conviction. By using a self-administered questionnaire, the researchers gathered the perceptions of 300 prepaid phone subscribers form four carriers. The findings show that there is a significant direct connection between quality of service and customer satisfaction. Furthermore, the results of the study also demonstrate that customer loyalty is important predictors of quality of service, switching costs, and conviction. Trust is the most crucial determinants of customer loyalty among these three precedents in the context of service-oriented enterprises.